Dynamics of 5-carboxylcytosine during hepatic differentiation: potential general role for active demethylation by DNA repair in lineage specification - Lewis, Lara C.; Lo, Peggy Cho Kiu; Foster, Jeremy M.; Dai, Nan; Correa, Ivan R.; Durczak, Paulina M.; Duncan, Gary; Ramsawhook, Ashley; Aithal, Guruprasad P.; Denning, Chris; Hannan, Nicholas R.F.; Ruzov, Alexey (Taylor & Francis, 2017)
Patterns of DNA methylation (5-methylcytosine, 5mC) are rearranged during differentiation contributing to the regulation of cell type-specific gene expression. TET proteins oxidise 5mC to 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC) and 5-carboxylcytosine (5caC). Both 5fC and 5caC can be recognised and excised from DNA by thymine-DNA glycosylase (TDG) followed by the subsequent incorporation of unmodified cytosine into the abasic site via the base excision repair (BER) pathway. We previously demonstrated that 5caC accumulates during lineage specification of neural stem cells (NSCs) suggesting that such active demethylation pathway is operative in this system, however it is still unknown if TDG/BER-dependent demethylation is utilised during other types of cellular differentiation. Here we analyse dynamics of the global levels of 5hmC and 5caC during differentiation of human pluripotent stem cells (hPSCs) towards hepatic endoderm. We show that, similar to differentiating NSCs, 5caC transiently accumulates during hepatic differentiation. The levels of 5caC increase during specification of foregut, peak at the stage of hepatic endoderm commitment and drop in differentiating cells concurrently with the onset of expression of Alpha Fetoprotein, a marker of committed hepatic progenitors. Moreover, we show that 5caC accumulates at promoter regions of several genes expressed during hepatic specification at differentiation stages corresponding to the commencement of their expression. Our data indicate that transient 5caC accumulation is a common feature of two different types (neural/glial and endoderm/hepatic) of cellular differentiation. This suggests that oxidation of 5mC may represent a general mechanism of rearrangement of 5mC profiles during lineage specification of somatic cells in mammals.